Child Marriage and Judicial Discretion: Analyzing the Impact of Marriage Dispensation Laws in Indonesia - nurulis, niaaja (Maliki Interdisciplinary Journal, 2025)
Child marriage remains a pressing issue in Indonesia, despite legal reforms designed to protect minors from early marriage. This study examines the practice of marriage dispensations, analyzing its legal foundations, socio-cultural influences, and economic determinants. The objective is to assess the extent to which marriage dispensation laws align with international child protection standards and to identify factors contributing to their persistent use (Julianto et al., 2025). Using a mixed-methods approach, the study integrates qualitative analysis of judicial decisions with quantitative examination of marriage dispensation trends across various regions. Primary data were collected from court records and interviews with judges, while secondary sources provided insights into socio-economic factors influencing child marriage.The findings reveal that the legal framework, particularly Law No. 16 of 2019, has not effectively curtailed child marriage due to judicial discretion in interpreting "urgent circumstances." Judges frequently consider factors such as family honor, economic hardship, and premarital pregnancy when granting dispensations, leading to inconsistent legal applications. Additionally, marriage dispensations contribute to negative educational, economic, and health outcomes for young brides, perpetuating cycles of poverty and gender inequality. These findings highlight the necessity for stricter legal definitions of "urgent circumstances," enhanced judicial training, and comprehensive community awareness campaigns to shift cultural perceptions of early marriage. Future policy initiatives should integrate legal reforms with economic and educational interventions to provide viable alternatives to child marriage. By adopting a multi-faceted approach, Indonesia can better align its legal practices with international human rights standards and strengthen child protection mechanisms.